Attenuation of Compulsive-Like Behavior Through Positive Allosteric Modulation of α4β2 Nicotinic Acetylcholine Receptors in Non-Induced Compulsive-Like Mice - Mitra, Swarup; Mucha, Mckenzie; Khatri, Shailesh N.; Glenon, Richard; Schulte, Marvin K.; Bult-Ito, Abel (Frontiers in Behavioral Neuroscience, 2017)
Nicotinic α4β2 receptors are the most abundant subtypes of nicotinic acetylcholine receptors (nAChRs) expressed in brain regions implicated in obsessive compulsive disorder (OCD). These receptors are known to modify normal and addictive behaviors by modulating neuronal excitability. Desformylflustrabromine (dFBr) is a novel, positive allosteric modulator (PAM) of HS (high acetylcholine sensitivity) and LS (low acetylcholine sensitivity) α4β2 nAChRs. The present study tested the hypothesis that positive allosteric modulation of α4β2 receptors by dFBr will attenuate compulsive-like behavior in a non-induced compulsive-like mouse model. Male mice (Mus musculus) selected for compulsive-like nesting (NB) behavior (48 animals; 12 per group) received acute (once) and chronic (every day for 32 days) subcutaneous injection of dFBr at 2, 4 and 6 mg/kg doses. Saline was used as a control (0 mg/kg). Compulsive-like NB was assessed after 1, 2, 3, 4, 5 and 24 hours, while compulsive-like marble burying (MB) and anxiety-like open field (OF) behaviors were performed 2 hours after dFBr administration. In the acute administration protocol, dFBr dose dependently attenuated NB and MB. Rapid effects (1-2 hours after drug administration) of dFBr on MB and NB were observed for the chronic administration which was in congruence with the acute study. Chronic administration also revealed sustained suppression of NB by dFBr following five weeks of treatment. In both the acute and chronic regimen dFBr did not modulate OF behaviors. This research demonstrates the novel role of positive allosteric modulation of α4β2 nicotinic receptors by dFBr as a translational potential for OCD.